Bentuk tindak tutur ilokusi pada film Sejuta Sayang ‎untuknya karya Herwin Novianto: Kajian pragmatik - Jambak, Mellinda Raswari (Maliki Interdisciplinary Journal, 2023)
In communicating requires understanding in order to run smoothly. The utterances spoken by the speaker to the speech partner have their own meaning or purpose according to the context used in the dialogue. This study examines a branch of pragmatics, namely speech acts. However, the speech act used is an illocutionary speech act. This study aims to analyze the forms of assertive, directive, expressive, commissive and declarative illocutionary acts in the film Sejuta Sayang Untuknya by Herwin Novianto. The object of study in this research is the dialogues of the characters in the film Sejuta Sayang Untuknya by Herwin Novianto. The method used is descriptive qualitative method. Using qualitative data and analyzing it descriptively. The theory used is one of pragmatic studies, namely speech acts. The results of the study obtained six data from the film One Million Love For Him by Herwin Novianto. Two data of assertive speech acts, two data of directive speech acts, two data of expressive speech acts, two data of commissive speech acts, and two data of declarative speech acts.